Weathering the storm: diagnosis and treatment of a life-threatening disseminated Nocardia otitidiscaviarum infection - Zhang, Li-Yan; Wang, Liang; Umar, Zeeshan; Huang, Yuan-Hong; Gu, Bing (Frontiers in Cellular and Infection Microbiology, 2024)
Nocardiosis demonstrates a temporal categorization that includes acute, subacute, and chronic stages alongside distinct typical localizations such as pulmonary, cutaneous, and disseminated forms. Disseminated nocardiosis, commonly caused by Nocardia asteroides, N. brasiliensis, and N. farcinica, continues to result in substantial morbidity and mortality. Herein, we report a life-threatening disseminated nocardiosis caused by Nocardia otitidiscaviarum in a patient with minimal change disease. This study emphasizes the difficulty in the diagnosis and treatment of unknown infections in clinical settings and highlights the important role played by laboratories in solving infectious diseases caused by rare pathogens.